2018
DOI: 10.3389/fgene.2018.00151
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Neuronal Transcription of Escargot, the Drosophila Gene Encoding a Snail-Type Transcription Factor, Promotes Longevity

Abstract: In recent years, several genes involved in complex neuron specification networks have been shown to control life span. However, information on these genes is scattered, and studies to discover new neuronal genes and gene cascades contributing to life span control are needed, especially because of the recognized role of the nervous system in governing homeostasis, aging, and longevity. Previously, we demonstrated that several genes that encode RNA polymerase II transcription factors and that are involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Transcript levels were measured as described in [15,16]. Total RNA for real-time reverse transcription quantitative PCR (RT-qPCR) was extracted from batches of 30 whole bodies of 3- to 5-day-old males and females using TRIzol reagent (Invitrogen, Carlsbad, CA, USA) and DNase I (Sigma-Aldrich, St. Louis, MO, USA) according to the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcript levels were measured as described in [15,16]. Total RNA for real-time reverse transcription quantitative PCR (RT-qPCR) was extracted from batches of 30 whole bodies of 3- to 5-day-old males and females using TRIzol reagent (Invitrogen, Carlsbad, CA, USA) and DNase I (Sigma-Aldrich, St. Louis, MO, USA) according to the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…First, GSK3 participates in the control of asymmetric neuroblast division. Earlier, we demonstrated that functional changes in several genes involved in the regulation of this developmental process, namely, aPKC encoding the GSK3 target, aPKC, escargot and inscutable , affect the lifespan of adult flies [14,15]. Moreover, our previous studies suggest that changes in gene expression at the embryonic stage can be responsible for an increase in adult lifespan due to yet unknown mechanisms that provide this carry-over effect [16].…”
Section: Introductionmentioning
confidence: 99%
“…The CDSs containing P-SSRs in the genomes of Homo sapiens, Mus musculus, Oryctolagus cuniculus, Tupaia chinensis, and Galeopterus variegatus were mainly enriched in transcription factors ( Figure 6B). Transcription factors, which bind preferentially to certain DNA sequences, play the central role of transcriptional regulation in all organisms (Imlay, 2015;Symonenko et al, 2018;Mejhert et al, 2020). In this study, the transcription factors containing SSRs were further identified from the annotation files and the results in Supplementary Table 11 by a Python script.…”
Section: Functional Analysis Of Cdss With P-ssrs In the Genomes Of Eumentioning
confidence: 99%
“…An early landmark study of gene expression in Drosophila indicated that adult flies differ dramatically in gene expression between sexes, but, within a given sex, gene expression is rather stable across different age classes [ 24 ]. As a consequence, many gene expression analyses in Drosophila combine flies differing in age by up to 15 days in a single sample, for example, [ 11 , 18 , 25 , 26 , 27 , 28 ]. Since several subsequent studies of senescence in Drosophila demonstrated considerable gene expression dynamics during aging [ 29 , 30 , 31 , 32 , 33 ], we were interested in scrutinizing the differences in gene expression between flies differing in age by as little as 24 h.…”
Section: Introductionmentioning
confidence: 99%